Use of protective antigen of Bacillus anthracis as a model recombinant antigen to evaluate toll-like receptors 2, 3, 4, 7 and 9 agonists in mice using established functional antibody assays, antigen-specific antibody assays and cellular assays. Issue 38 (9th September 2022) - Inglefield, Jon; Catania, Jason; Harris, Andrea; Hickey, Thomas; Ma, Zhidong; Minang, Jacob; Baranji, Katalin; Spangler, Tarl; Look, Jee; Ruiz, Christian; Lu, Hang; Alleva, David; et al.
Highlights: TLR agonists in mice predominantly are stimulatory regardless of formulation (Alhydrogel or squalene) Functional (toxin-neutralizing) antigen-specific antibodies are a functional subset of IgG antigen-specific serum antibodies. Ratios for antigen-specific IgG1:IgG2a redirection in mice were established using quantitative ELISA achieving 1:1 for profound redirection effect, 10:1 for partial redirection and 40:1 for an Alhydrogel vaccine with no redirection. Overall, an accelerated immunization regimen (2 immunizations 7 days apart) had less negative effect upon vaccines that contained CPG 7909. Abstract: Toll-like receptor (TLR) agonists can act as immune stimulants alone or as part of alum or oil formulations. Humoral and cellular immune responses were utilized to assess quantitative and qualitative immune response enhancement by TLR agonists using recombinant protective antigen (rPA) of B. anthracis as a model antigen. To rPA, combined with aluminum hydroxide (Alhydrogel; Al(OH)3) or squalene (AddaVax™), was added one of 7 TLR agonists: TLR2 agonist Pam3CysSK4 (PamS), TLR3 agonist double stranded polyinosinic:polycytidylic acid (PolyIC), TLR4 agonists Monophosphoryl lipid A (MPLA) or glucopyranosyl lipid A (GLA), TLR7-8 agonists 3M−052 or Resiquimod (Resiq), or TLR9 agonist CPG 7909 (CPG). CD-1 or BALB/c mice received two intraperitoneal or intramuscular immunizations 14 days apart, followed by serum or spleen sampling 14 days later. All TLR agonists except PamS induced high levels of B. anthracis lethal toxin-neutralizing antibodies and immunoglobulin G (IgG) anti-PA. Some responses were >100-fold higher than those without a TLR agonist, and IP delivery (0.5 mL) induced higher TLR-mediated antibody response increases compared to IM delivery (0.05 mL). TLR7-8 and TLR9 agonists induced profound shifts of IgG anti-PA response to IgG2a or IgG2b. Compared to the 14-day immunization schedule, use of a shortened immunization schedule of only 7 days between prime and boost found that TLR9 agonist CPG in a squalene formulation maintained higher interferon-γ-positive cells than TLR4 agonist GLA. Variability in antibody responses was lower in BALB/c mice than CD-1 mice but antibody responses were higher in CD-1 mice. Lower serum 50% effective concentration (EC50) values were found for rPA-agonist formulations and squalene formulations compared to Al(OH)3 formulations. Lower EC50 values also were associated with low frequency detection of linear peptide epitopes. In summary, TLR agonists elicited cellular immune responses and markedly boosted humoral responses.